Legal Reconstruction of Witness and Victim Protection Institutions in the Criminal Justice System - Chalil, Sri Mulyati; Suhardini, Eni Dasuki; Durahman, Dani; Tejo, Eko Susanto (JURNAL AKTA, 2025)
This paper aims to explore the urgency of reconstructing the institutional role of the Witness and Victim Protection Agency (LPSK) within Indonesia’s criminal justice system. Using a normative and empirical legal research methods, which is done by literature review, field exploration, and analysis, it builds an accurate and concrete model for implementing the construction of the position of the LPSK in the current criminal justice system. This study found that bureaucratic challenges—such as financial limitations, inadequate human resources, and institutional stagnation—have constrained the justice system’s ability to function equitably. These conditions often lead to the centralization of investigative power and a compartmentalized system in which oversight is limited and reactive. Within this context, LPSK holds potential as a horizontal oversight mechanism, offering checks on investigators’ authority and ensuring victim and witness rights are safeguarded during proceedings. This paper further analyzes how the Criminal Procedure Code anticipates horizontal supervision between law enforcement agencies, particularly between investigators and public prosecutors, and how LPSK can contribute to this oversight structure. However, limitations in institutional capacity and the centralized nature of LPSK pose challenges to its accessibility and effectiveness. Strengthening LPSK’s institutional capacity and expanding its regional presence are critical for responding to the growing demand for witness and victim protection, including in cases involving gross human rights violations. This study underscores the need for systemic reform and political will to ensure that protection of witnesses and victims becomes an integral part of a due process-oriented criminal justice system in Indonesia.